A novel double modification to enhance electrochemical performance of LiNi0.5Co0.2Mn0.3O2 by substituting Ce for Co site. (20th September 2021) - Feng, Liwei; Liu, Yan; Qin, Wenchao; Yang, Zihao; Liu, Jinfeng
Abstract: Ce substitution can not only make Ce 3+ doped into the crystal lattice, but stabilize the bulk structure by means of robust Ce-O bond, and form ceria coating layer at outer surface to protect matrix material. The influence of different Ce content on atomic occupation, lattice parameters and Li + / Ni 2+ mixing extent were studied at length by Rietveld refinement. Profiting from the synergistic effect of lithium defects in ceria and enlarged crystal plane spacing, Ce 0.15%-NCM has superior electrochemical performance. Cycled at 5 C, Ce 0.15%-NCM has superior initial discharge capacity of 138.7 mAhg −1 and capacity retention of 83.99% after 200 cycles. So far as to the full-cells state, Ce 0.15%-NCM delivers the initial energy density of 406 Wh kg −1 and 72.94% retention after 200 cycles. Combined with the results of HRTEM and EDS spectrum, the cycled electrodes were investigated, and the mechanism of Ce modification at high potential cycling was further studied. Graphical abstract: Image, graphical abstract